Medication administration errors among children admitted at a Regional Hospital in Northern Ghana - Francis Kwaku Wuni; Aiden Suntaa Saanwie; Emmanuel Kofi Dzotsi; Samuel Aborah; Saffoh Samuel Amoateng; Zakaria Yakubu; Catherine Anyoka; Peter Nbaltoe Unawari (Elsevier, 2024)
Background: Errors in medication administration have a number of detrimental effects, including delayed healing, drug resistance, morbidity, and even mortality, particularly in children. However, there are limited empirical data on the incidence of medication administration errors experienced by children admitted to healthcare facilities in Ghana. Methods: An analytic cross-sectional design was used to obtain prospective data from 399 sick children admitted to the Upper East Regional Hospital using a convenient sampling. Both descriptive and inferential statistical analyses such as Pearson chi-square tests and binary logistic regression, were also conducted. Results: The incidence of medication administration errors was 65.9 %. The intravenous route of medication was the most common route involved in medication administration errors (48.1 %). An incorrect frequency of drug administration (41.9 %) was the most common type of error. There were significant correlations between the occurrence of medication administration errors and hospital ward ((χ2 =13.1, p < 0.001), patient' age ((χ2 = 19.254, p < 0.001) and patient' weight ((χ2 = 5.740, p < 0.05). Conclusion: The incidence of medication administration errors is very high among pediatric inpatients in healthcare facilities.